Digitalization and the transformation of labor demand: macroeconomic consequences ("Journal "U". Economy. Management. Finance.", 2026)
The article examines the impact of digitalization processes, particularly the development of artificial intelligence and platform employment, on the transformation of labor demand. Based on an econometric analysis of panel data across sectors of the Russian economy for 2019–2026, a multidirectional dynamic in the demand for skilled and unskilled labor is identified, along with the macroeconomic consequences of structural shifts in the labor market.
Keywords: digitalization; transformation of labor demand; artificial intelligence; gig economy; labor market; macroeconomic consequences